1981
DOI: 10.1007/bf00431763
|View full text |Cite
|
Sign up to set email alerts
|

The alcohol facilitation effect on memory: A dose-response study

Abstract: Sixteen normal male subjects participated in four sessions where they studied a set of pictures followed by either placebo, 0.025, 0.50, or 1.0 ml/kg alcohol. Later, when sober, recognition memory was tested. These doses resulted in peak blood alcohol concentrations (BAC) of 0.00, 0.018, 0.034, and 0.067 g/100 ml, respectively. The 1.0 and 0.50 ml/kg doses significantly improved memory for pictures studied before drinking. Alcohol appears to enhance memory directly rather than indirectly via a reduction in int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
4

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 25 publications
5
72
4
Order By: Relevance
“…More recently, Parker, Birnbaum, Weingartner, Hartley, Stillman, and Wyatt (1980) and Parker, Morihisa, Wyatt, Schwartz, Weingartner, and Stillman (1981) found that subjects who viewed a series of scenic slides just before drinking alcohol later remembered the slides significantly better than did subjects who received a placebo. Parker et al (1981) concluded that this retrograde enhancement of memory is due to a facilitation of the trace consolidation process by the alcohol. Although their interpretation provides an explanation for the present data, the present results may also be explained easily by an interference mechanism: When recalling the practice list, the drugged subjects should have experienced much less retroactive interference than did the placebo subjects because the drugged subjects had learned so little of the postdrug material.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, Parker, Birnbaum, Weingartner, Hartley, Stillman, and Wyatt (1980) and Parker, Morihisa, Wyatt, Schwartz, Weingartner, and Stillman (1981) found that subjects who viewed a series of scenic slides just before drinking alcohol later remembered the slides significantly better than did subjects who received a placebo. Parker et al (1981) concluded that this retrograde enhancement of memory is due to a facilitation of the trace consolidation process by the alcohol. Although their interpretation provides an explanation for the present data, the present results may also be explained easily by an interference mechanism: When recalling the practice list, the drugged subjects should have experienced much less retroactive interference than did the placebo subjects because the drugged subjects had learned so little of the postdrug material.…”
Section: Discussionmentioning
confidence: 98%
“…7. Numerous studies have established that at concentrations produced by the ingestion of one to two drinks (5-10 mM), EtOH causes paradoxical excitatory effects, including memory facilitation (43)(44)(45). Importantly, an increase in the spontaneous firing rate of single units in the dorsal hippocampus has been demonstrated after injection of low doses of EtOH into rats (46).…”
Section: Discussionmentioning
confidence: 99%
“…One interesting result with respect to the recall memory literature is that a number of studies identified facilitative effects of alcohol on recall performance (Kalin, 1964;Lamberty, Beckwith, Petros, and Ross, 1990), recognition performance (Parker, Birnbaum, Weingartner, Hartley, Stillman, and Wyatt, 1980;Parker, Morihisa, Wyatt, Schwartz, Weingartner, and Stillman, 1981), and continuous processing (Carpenter and Ross, 1965). The alcohol doses in these studies ranged from .03 to 0.1%.…”
Section: Acute Effects Of Alcohol On Task Performancementioning
confidence: 99%